Best Practices in Endangered Species Recovery Planning: Lessons for the Conservation of Maine’s Atlantic Salmon - O’Connor, Raymond; Owen, Ray; Rhymer, Judith (Maine Policy Review, 2000)
The call for federal listing of Atlantic salmon as endangered implies that such action will result in a recovery plan for the species that is superior to Maine ’s Atlantic Salmon Conservation Plan. In this article the authors compare the Maine plan against the findings of a recent review of Endangered Species Act recovery plans. The review, conducted by the Society for Conservation Biology in collaboration with the U.S. Fish and Wildlife Service, assessed the quality of a national sample of Endangered Species Act recovery plans with the intention of identifying “best practice.” By comparing the Maine plan to the findings of this review, the authors indicate areas where Maine’s plan is strong and suggest areas where there may be room for improvement.